Lessons Learned From a Physical Activity Intervention in Psychiatric Treatment: Patient, Staff, and Leader Perspectives - Sørensen, Marit; Bentzen, Marte; Farholm, Anders (Frontiers in Psychiatry, 2020)
Objective: To explore how the implementation of a motivational physical activity intervention for inpatients with severe mental illness was experienced by patients, staff, and leaders at a psychiatric institution. Method: After the intervention individual semi-structured interviews were conducted with patients (n=6) and staff (n=6), and a focus group interview was conducted with the leaders (n=4). Results: All had a positive view on physical activity (PA) as part of psychiatric treatment, thinking it would benefit the patients' health There were some differences among the groups as to the importance of PA relative to traditional treatments. Positive outcomes were reported from all three groups, but with different foci. The patients and the staff underscored the importance of physical activity professionals in order to achieve high quality activities, whereas the leaders, due to restraints in resources, could not prioritizse to hire physical activity professionals. Conclusion: PA was considered a positive part of treatment. Ideas about what it takes to obtain the potential physical, mental and social benefits of PA differed between patients, the staff involved, and the leaders. Having staff with PA as a primary responsibility and with sufficient competence as PA instructors seems to be important.